Exploration of an Instrument to Measure the Entrepreneurial Profile of Management Students - Rossi Ortiz, Ricardo (2024)
The Global Entrepreneurship Monitor reports that Peru ranks fourth in Latin America and eighth worldwide in entrepreneurial intention among university students. However, many of these students face difficulties in trying to start their own businesses after gra[1]duation, which is reflected in the Peruvian economy due to a heavy reliance on microen[1]terprises linked to informal commerce. In this context, the university plays a crucial role. This study designed an instrument for the practical assessment of the entrepreneurial profile of business administration students. The instrument was applied to 375 students. The results obtained, through an exploratory factor analysis, condensed the 20 items into a single dimension with high internal consistency, demonstrating very high reliability. The promotion of entrepreneurship in university education involves identifying skills and competencies relevant to each context, supported by various theories, and revealing the need to adjust the grid. Although the instrument developed demonstrated robustness and reliability, its limitation in terms of application in a single private university is re[1]cognized. Therefore, it is suggested to carry out continuous measurements to validate its relevance and implement it in other university institutions.